Farmers’ Perceptions on Dairy Development Strategies in Vavuniya District, Sri Lanka - Kamshajini, R.; Sooriyakumar, K.; Sivashankar, S. (University of Jaffna, 2020)
Improving milk production in Northern Province is one of the main constituents of dairy rural life. Dairy farmers confront the challenges such as lack of abandoned land, lack of grazing land, the low success rate of artificial insemination, lack of awareness of new technology and the annual total amount of milk entry to dairy market is not enough. Vavuniya is one of the main milk producing and cattle breeding districts. This study investigates farmer’s willingness to pay for different dairy development strategies, their priority among the development strategies and the impact of socioeconomic demographic characters of farmer on the perceptions of dairy development strategies. For this study, 200 farmers were randomly selected from Vavuniya district. Choice modelling was employed and conditional logit models were developed to estimate farmer’s willingness to pay for different dairy development strategies. The result of this study indicates that farmers are willing to pay for all dairy development strategies and their priority order among development strategies is as follows: training on silage making, milk collection in morning and evening, milk collection centre within 2 km and increase the success rate of artificial insemination. Farmer’s income and education level positively influence the willingness to pay for training on silage making and also farmer’s education level has positive impact on the willingness to pay for milk collection in morning and evening. Female farmers are willing to pay more for training on silage making than male farmers. Finding of this study would assist various planners and authorities in formulating suitable dairy development strategies and appropriate fees for the services provided by the Department of Animal Production and Health to increase milk production in Vavuniya district and utilize the services in effective way.
Keywords: Choice Modelling; Conditional Logit Model; Dairy Development strategies